Deciphering the mechanism of Tinospora cordifolia extract on Th17 cells through in-depth transcriptomic profiling and in silico analysis - Nandan, Amrita; Sharma, Vishwas; Banerjee, Prodyot; Sadasivam, Kannan; Venkatesan, Subramanian; Prasher, Bhavana (Frontiers in Pharmacology, 2023)
ABSTRACT Naive CD4+ T cells differentiate into effector (Th1, Th2, Th17) cells and immunosuppressive (Treg) cells upon antigenic stimulation in the presence of a specific cytokine milieu. The T cell in vitro culture system provides a very efficient model to study compounds’ therapeutic activity and mechanism of action. Tinospora cordifolia (Willd.) Hook.f. & Thomson (Family. Menispermaceae) (TC) is one of the widely used drugs in Ayurveda (ancient Indian system of medicine) for various ailments such as inflammatory conditions, autoimmune disorders, and cancer as well as for promoting general health. In vitro and in vivo studies on immune cells comprising dendritic cells, macrophages, and B cells suggest its immune-modulating abilities. However, to date, the effect of TC on individual purified and polarized T cell subsets has not been studied. Studying drug effects on T cell subsets is needed to understand their immunomodulatory mechanism and to develop treatments for diseases linked with T cell abnormalities. In this study, we examined the immunomodulatory activity of TC on primary CD4+ T cells, i.e., Th1, Th17, and iTreg cells. An aqueous extract of TC was non-cytotoxic at concentrations below 1500 µg/ mL and moderately inhibited the proliferation of naive CD4+ T cells stimulated with anti-CD3ε and anti-CD28 for 96 h. TC treatment of naive CD4+ T cells differentiated under Th17-polarizing conditions exhibited reduced frequency of IL-17 producing cells with inhibition of differentiation and proliferation. For the first time, in-depth genome-wide expression profiling of TC treated naive CD4+ T cells, polarized to Th17 cells, suggests the broad-spectrum activity of TC. It shows inhibition of the cytokine-receptor signaling pathway, majorly via the JAK-STAT signaling pathway, subsequently causing inhibition of Th17 cell differentiation, proliferation, and effector function. Additionally, the molecular docking studies of the 69 metabolites of TC further substantiate the inhibitory activity of TC via the cytokine-receptor signaling pathway. Furthermore, in vitro polarized Th1 and iTreg cells treated with TC extract also showed reduced IFN-γ production and FoxP3 expression, respectively. This study provides insight into the plausible mechanism/s of anti-inflammatory activity of TC involving T cells, mainly effective in Th17-associated autoimmune and inflammatory diseases.